2021
DOI: 10.3233/jpd-202465
|View full text |Cite
|
Sign up to set email alerts
|

The Human Hippocampus in Parkinson’s Disease: An Integrative Stereological and Proteomic Study

Abstract: Background: Parkinson’s disease (PD) is a prevalent neurodegenerative disease that is pathologically described as a six-stage α-synucleinopathy. In stage 4, α-synuclein reaches the hippocampus, inducing cognitive deficits, from which it progresses to the isocortex, leading to dementia. Among hippocampal fields, cornu ammonis 2 is particularly affected by this α-synucleinopathy and critical for cognitive decline. Volumetric studies using magnetic resonance imaging have produced controversial results, with only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…420300-9900), and quantification was performed with a 63× objective (Zeiss Plan-Apochromat 63×/1.4 oil DIC, Ref. 420782–9900) ( Figure 1 ) [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…420300-9900), and quantification was performed with a 63× objective (Zeiss Plan-Apochromat 63×/1.4 oil DIC, Ref. 420782–9900) ( Figure 1 ) [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The total protein concentration was measured with a Qubit fluorimetric protein assay (Thermo Fisher Scientific, Waltham, MA, USA). Forty micrograms of protein from each sample were digested with trypsin, and massive protein relative quantitation was conducted using the SWATH-MS approach, as previously described [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…420782-9900); Iba-1, LBs, LNs, and overlapping areas; and GFAP, LBs, LNs, and overlapping areas (Plan Apochromat, 40X/0.95, Ref. in PD samples (Flores-Cuadrado et al, 2021;Villar-Conde et al, 2021). The total area fraction of different cell populations was calculated by the sum of markers with and without overlapping, except for AONb data in the NeuN study, which was obtained directly by quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Parkinson’s disease is characterized by progressive neurodegeneration ( Poewe et al, 2017 ). Recently, neurodegeneration was reported in the human olfactory bulb ( Flores-Cuadrado et al, 2021 ), whereas it has not been reported in other brain areas, such as the hippocampus ( Villar-Conde et al, 2021 ). To date and to the best of our knowledge, only two studies have analyzed the neuronal population of AONb in PD.…”
Section: Introductionmentioning
confidence: 99%
“…According to the prion hypothesis, α-synuclein spreads through neuronal connections and glia [ 111 ]. This propagation in the fourth stage of neuropathological course related to PD [ 112 ] reaches the hippocampus [ 113 ], producing changes in the proteins associated with synaptic structures and altering neuronal communication and function [ 114 ]. Owing to compensation and plasticity effects, during the progression of PD, training in daily living activities has been shown to restore neural circuits for movement, allowing intact nervous systems [ 115 ].…”
Section: Ameliorating Mitochondrial Dysfunction In Parkinson’s Diseas...mentioning
confidence: 99%